Barriers to entry in frequency-regulation services markets: Review of the status quo and options for improvements. (January 2018) - Borne, Olivier; Korte, Klaas; Perez, Yannick; Petit, Marc; Purkus, Alexandra
Abstract: As the share of intermittent renewable energy sources increases, it will be necessary to increase the volume of frequency-regulation reserves. New sources of reserves can be found in distributed energy resources: controllable loads, Electric Vehicles (EVs), distributed generation units. However, it is necessary to adapt the frequency-regulation reserve market design to allow these new resources to participate through new market players known as "aggregators". The aim of this paper is to provide a modular framework to analyze frequency regulation markets or mechanisms in order i) to identify barriers to entry for aggregators and ii) to identify some options to overcome these barriers. A case study of the situation in 2016 of four major European frequency regulation markets is performed to show how this framework could be used by aggregators or policy-makers.